Patient and provider determinants for receipt of three dimensions of respectful maternity care in Kigoma Region, Tanzania-April-July, 2016 - M. M. Dynes; E. Twentyman; L. Kelly; G. Maro; A. A. Msuya; S. Dominico; P. Chaote; R. Rusibamayila; F. Serbanescu (BMC, 2018)
Abstract Background Lack of respectful maternity care (RMC) is increasingly recognized as a human rights issue and a key deterrent to women seeking facility-based deliveries. Ensuring facility-based RMC is essential for improving maternal and neonatal health, especially in sub-Saharan African countries where mortality and non-skilled delivery care remain high. Few studies have attempted to quantitatively identify patient and delivery factors associated with RMC, and none has modeled the influence of provider characteristics on RMC. This study aims to help fill these gaps through collection and analysis of interviews linked between clients and providers, allowing for description of both patient and provider characteristics and their association with receipt of RMC. Methods We conducted cross-sectional surveys across 61 facilities in Kigoma Region, Tanzania, from April to July 2016. Measures of RMC were developed using 21-items in a Principal Components Analysis (PCA). We conducted multilevel, mixed effects generalized linear regression analyses on matched data from 249 providers and 935 post-delivery clients. The outcomes of interest included three dimensions of RMC-Friendliness/Comfort/Attention; Information/Consent; and Non-abuse/Kindness-developed from the first three components of PCA. Significance level was set at p < 0.05. Results Significant client-level determinants for perceived Friendliness/Comfort/Attention RMC included age (30-39 versus 15-19 years: Coefficient [Coef] 0.63; 40-49 versus 15-19 years: Coef 0.79) and self-reported complications (reported complications versus did not: Coef − 0.41). Significant provider-level determinants included perception of fair pay (Perceives fair pay versus unfair pay: Coef 0.46), cadre (Nurses/midwives versus Clinicians: Coef − 0.46), and number of deliveries in the last month (11-20 versus < 11 deliveries: Coef − 0.35). Significant client-level determinants for Information/Consent RMC included labor companionship (Companion versus none: Coef 0.37) and religiosity (Attends services at least weekly versus less often: Coef − 0.31). Significant provider-level determinants included perception of fair pay (Perceives fair pay versus unfair: Coef 0.37), weekly work hours (Coef 0.01), and age (30-39 versus 20-29 years: Coef − 0.34; 40-49 versus 20-29 years: Coef − 0.58). Significant provider-level determinants for Non-abuse/Kindness RMC included the predictors of age (age 50+ versus 20-29 years: Coef 0.34) and access to electronic mentoring (Access to two mentoring types versus none: Coef 0.37). Conclusions These findings illustrate the value of including both client and provider information in the analysis of RMC. Strategies that address provider-level determinants of RMC (such as equitable pay, work environment, access to mentoring platforms) may improve RMC and subsequently address uptake of facility delivery.